PENGARUH MODEL PEMBELAJARAN THINK PAIR SHARE BERBASIS MULTIMEDIA TERHADAP KOMPETENSI PENGETAHUAN IPS SISWA KELAS IV - Kadek Rahayu Putri (Indonesian Journal Of Educational Research and Review, 2018)
The purpose of this research was aimed to know about the affect of cooperative learning model type of think pair share based on multimedia against the competence social science knowledge of 4th grade class elementary school of Gugus Letda Made Putra at North Denpasar in the of year 2017/2018. This research was a quasi experiment with non-equivalent design. The population of this research was 393 students. The sample was taken by group sampling technique with disorganize class. The sample in this research was 4th grade class c elementary school 2 Dangin Puri as experimental group with 33 students and 4th grade class b elementary school 5 Tonja with 41 students as control group. The instrument which used collecting data which is validating objective test 36 rounds. In the end of this research gain score data normalization competence of social science knowledge analyzed with t-test. Of the analysis the result are significant difference between social science competence group experiment and group control. That things proven by result t-test that tcount = 6,193 > ttabel = 1,993 with significant criteria level 5% and dk = 72. Average competence of social experimental group x̅ = 0,59 > x̅ = 0,41 average competence of social control group. Then it could be learning model of type cooperative think pair share based on multimedia is affected with social science students competence fourth grade class elementary school of Gugus Letda Made Putra North Denpasar 2017/2018. Key Words: think pair share, multimedia, social science competence